2019
DOI: 10.1111/eff.12510
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age and reservoir characteristics as predictors of trait composition in Neotropical reservoir fish assemblages

Abstract: One of the main impacts on aquatic environments is the alteration of flow regime, usually caused by dam construction. This impact changes the dynamics and functioning of the environment. We aimed to evaluate changes in the composition of functional traits of fish assemblages from 29 reservoirs of different chronological ages. We assessed if there were any alterations in trophic state of these reservoirs according to their ages (chronological variable). Then, we evaluated the relationship between functional tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…(2017) and Muniz, Santos, et al. (2019) found that older reservoirs tended to have more species that live in the benthopelagic region and present parental care, but on a smaller spatial scale. As we expanded the spatial scale in this study, we believed that encompassing a wider range of reservoir ages separated our results from theirs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2017) and Muniz, Santos, et al. (2019) found that older reservoirs tended to have more species that live in the benthopelagic region and present parental care, but on a smaller spatial scale. As we expanded the spatial scale in this study, we believed that encompassing a wider range of reservoir ages separated our results from theirs.…”
Section: Discussionmentioning
confidence: 97%
“…Intuitively, we may expect older and smaller reservoirs, which have been under stronger anthropogenic pressures, to present decreased functional diversity. This would emerge because reservoir ageing can increase the dominance of some species (Agostinho et al., 2016; Muniz et al., 2019), whereas smaller reservoirs may carry fewer species and therefore more simplified ecological functions, and higher human pressure may have negative impacts on each local ichthyofauna. For climate, in contrast, we may expect higher functional diversity in reservoirs in warmer and wetter locales because of the documented positive relationship between species and energy that applies to many freshwater organisms, including fish (Bailly et al., 2016; Oberdoff et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Functional traits were selected using the relationships of the parents with ecosystem and community functions that are linked to local environmental drivers and the physiological processes allowing species to cope with abiotic conditions and resource availability (Rosado et al., 2013; Winemiller et al., 2015). We selected some classes of traits that are especially relevant to reservoirs (Muniz et al., 2020), including those related to reproductive strategy, food and habitat use (Table 1). Although not a functional trait, we included the origin of the species (native or non‐native) in the analysis because of its ecological importance (Vitule et al., 2012); the degree of invasive species is correlated with changes in functional diversity (Milardi et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, among the causes of global biodiversity loss, exotic invasions are often the most important (Leprieur et al., 2008; Sala et al., 2000), and an increase in the abundance of non‐native species is associated with decreases in ecosystem services (Attayde et al., 2011; Hoeinghaus et al., 2009). These functional characteristics were obtained from the literature or estimated based on species anatomy (Supporting Information S1; Muniz et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…rheophilic species) (Herbold & Moyle, 1986; Havel, Lee & Vander Zanden, 2005; Liew, Tan & Yeo, 2016). These impacts also change over time – a process called the ‘ageing effect’ – and are related to a reduction in the abundance of native top predators, mean size of species and overall species richness, particularly of rheophilic species, at later stages (Agostinho et al, 1999; Gido, Matthews & Wolfinbarger, 2000; Muniz et al, 2020). Despite the impacts of river damming on native fish faunas and, consequently, on artisanal fisheries, hydropower is widely developed worldwide as the primary source of electricity generation even today (Rubio & Tafunell, 2014; Apergis et al, 2016; Winemiller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%